A taxonomic revision of Hypogastrura crassaegranulata (Stach, 1949) (Collembola, Hypogastruridae) - Skarżyński, Dariusz (Zootaxa, 2006)
The polytypic species Hypogastrura crassaegranulata (Stach, 1949) is revised, mostly based on types. H. crassaegranulata dobsinensis (Stach, 1949) is synonymized with H. crassaegranulata sensu nov. and H. crassaegranulata estaranhensis Cassagnau, 1959 and H. crassaegranulata burgundiana Gisin, 1960 are synonymized with H. franconiana stat. nov. H. crassaegranulata carpatica Nosek, 1962 is recognized as a distinct species. Achorutes schäfferi Carl, 1901 (= A. affinis Schäffer, 1900), suspected as identical with H. crassaegranulata franconiana, is considered as a probable synonym of H. purpurescens (Lubbock, 1867). Redescriptions are provided and lectotypes are designated for H. crassaegranulata (Stach, 1949) sensu nov. and H. franconiana (Stach, 1949) stat. nov.